Application issues for large-area electrochromic windows in commercial buildings - Eleanor S. Lee; Dennis L. DiBartolomeo (Solar Energy Materials and Solar Cells, 2002)
Projections of performance from small-area devices to large-area windows and enterprise marketing have created high expectations for electrochromic glazings. As a result, this paper seeks to precipitate an objective dialog between material scientists and building-application scientists to determine whether actual large-area electrochromic devices will result in significant performance benefits and what material improvements are needed, if any, to make electrochromics more practical for commercial building applications. Few in situ tests have been conducted with large-area electrochromic windows applied in buildings. This study presents monitored results from a full-scale field test of large-area electrochromic windows to illustrate how this technology will perform in commercial buildings. The visible transmittance (T v ) of the installed electrochromic ranged from 0.11 to 0.38. The data are limited to the winter period for a south-east-facing window. The effect of actual device performance on lighting energy use, direct sun control, discomfort glare, and interior illumination is discussed. No mechanical system loads were monitored. These data demonstrate the use of electrochromics in a moderate climate and focus on the most restrictive visual task: computer use in offices. Through this small demonstration, we were able to determine that electrochromic windows can indeed provide unmitigated transparent views and a level of dynamic illumination control never before seen in architectural glazing materials. Daily lighting energy use was 6-24% less compared to the 11%-glazing, with improved interior brightness levels. Daily lighting energy use was 3% less to 13% more compared to the 38%-glazing, with improved window brightness control. The electrochromic window may not be able to fulfill both energy-efficiency and visual comfort objectives when low winter direct sun is present, particularly for computer tasks using cathode-ray tube (CRT) displays. However, window and architectural design as well as electrochromic control options are suggested as methods to broaden the applicability of electrochromics for commercial buildings. Without further modification, its applicability is expected to be limited during cold winter periods due to its slow switching speed. © 2002 Elsevier Science B.V. All rights reserved.